2,4-Dichlorophenoxyacetic acid (2,4-D) degradation promoted by nanoparticulate zerovalent iron (nZVI) in aerobic suspensions - Correia de Velosa, Adriana [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Elsevier, 2013)
Reactive species generated by Fe0 oxidation promoted by O2 (catalyzed or not by ligands) are able to degrade contaminant compounds like the herbicide 2,4-dichlorophenoxyacetic acid. The degradation of 2,4-D was influenced by the concentrations of zero valent iron (ZVI) and different ligands, as well as by pH. In the absence of ligands, the highest 2,4-D degradation rate was obtained at pH 3, while the highest percentage degradation (50%) was achieved at pH 5 after 120 min of reaction. Among the ligands studied (DTPA, EDTA, glycine, oxalate, and citrate), only ethylenediaminetetraacetic acid (EDTA) and diethylenetriaminepentaacetic acid (DTPA) significantly enhanced oxidation of 2,4-D. This increase in oxidation was observed at all pH values tested (including neutral to alkaline conditions), indicating the feasibility of the technique for treatment of contaminated water. In the presence of EDTA, the oxidation rate was greater at pH 3 than at pH 5 or 7. Increasing the EDTA concentration increased the rate and percentage of 2,4-D degradation, however increasing the Fe0 concentration resulted in the opposite behavior. It was found that degradation of EDTA and 2,4-D occurred simultaneously, and that the new methodology avoided any 2,4-D removal by adsorption/coprecipitation. © 2013 Elsevier Ltd.
Keywords: 2,4-D; DTPA; EDTA; Metallic iron; Nanoparticles; 2,4 dichlorophenoxyacetic acid; citric acid; edetic acid; glycine; iron derivative; nanoparticle; oxalic acid; pentetic acid; unclassified drug; zero valent iron; acetic acid; adsorption; alkalinity; biodegradation; catalysis; concentration (composition); ligand; oxic conditions; oxidation; oxygen; particulate matter; pH; pollutant removal; pollution effect; precipitation (chemistry); water treatment; acidity; concentration (parameters); controlled study; degradation; degradation kinetics; dissolution; precipitation; reaction time; water contamination